2011
DOI: 10.1111/j.1463-5224.2011.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ocular findings in cows with malignant catarrhal fever: ocular disease progression and outcome in 25 cases (2007–2010)

Abstract: The degree of corneal edema at first examination had no prognostic value for the disease outcome. The results of this study suggest that the progression of corneal edema correlates well with disease outcome, and that nonimprovement of uveitis is a bad prognostic sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…25,118 Currently, there is renewed interest in vaccination for this group of viruses, a goal long thought out of reach due to discouraging results in the 1970s and 1980s. 32,75,118,125,126 It is now clear that some dead-end host species recover, 92,93,153 corroborating clinical suspicions from the late 1920s and early 1930s that MCF is not invariably fatal. Important differences exist between the ecology of sheep-and wildebeest-associated MCF.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…25,118 Currently, there is renewed interest in vaccination for this group of viruses, a goal long thought out of reach due to discouraging results in the 1970s and 1980s. 32,75,118,125,126 It is now clear that some dead-end host species recover, 92,93,153 corroborating clinical suspicions from the late 1920s and early 1930s that MCF is not invariably fatal. Important differences exist between the ecology of sheep-and wildebeest-associated MCF.…”
mentioning
confidence: 78%
“…With the availability of serological and molecular diagnostic assays, it is clear that a fraction of acutely affected cattle recover. 92,93,153 Cattle surviving acute MCF generally have chronic lesions in medium-caliber arteries and in cornea. 92 Vascular lesions consist of proliferative arteriopathy with varying degrees of recanalization.…”
Section: Mcf In Domestic Cattlementioning
confidence: 99%
“…Malignant catarrhal fever (MCF) is a lethal infection of many species of Bovidae and Cervidae caused by a member of the Macavirus genus in the Gammaherpesvirinae subfamily (1,2,3). Alcelaphine herpesvirus type 1 (AlHV-1) and ovine herpesvirus type 2 are the major causative agents responsible for wildebeest-associated MCF and sheep-associated MCF, respectively (1,3). The AlHV-1 is endemic in wildebeest, in which it causes a subclinical infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Alcelaphine herpesvirus type 1 (AlHV-1) and ovine herpesvirus type 2 are the major causative agents responsible for wildebeest-associated MCF and sheep-associated MCF, respectively (1,3). The AlHV-1 is endemic in wildebeest, in which it causes a subclinical infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Typical signs of the head and eye form are opacity of the cornea, with a narrow grey ring at the corneo-scleral junction. A study conducted to investigate a possible correlation between the severity and progression of certain typical clinical signs and disease outcome indicated that in the surviving cases there was improvement in uveitis and no deterioration of corneal oedema and which usually worsens in fatal cases as the disease progresses thus concluding that the progression of corneal edema correlates well with disease outcome, and that non improvement of uveitis is a bad prognostic sign [91]. The characteristics of the head and eye form include extreme dejection, agalactia, high fever (41-41°C), rapid pulse rate (100-120 bpm), mucopurulent nasal discharge ( Fig.…”
Section: Clinical Signs and Pathologymentioning
confidence: 99%